Embodied texts : symbolist playwright-dancer collaborations - Fleischer, Mary (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2007)
"Embodied Texts: Symbolist Playwright-Dancer Collaborations explores the relationship between Symbolist theatre and early modern dance across Europe from the 1890s through the 1930s. Gabriele D'Annunzio's projects with Ida Rubinstein; Hugo von Hofmannsthal's pantomimes for Grete Wiesenthal; W.B. Yeats's work with Michio Ito and Ninette de Valois; and Paul Claudel's collaborations with Jean Borlin and the Ballets Suedois are studied in depth to shed new light on an evolving dance-theatre form within Symbolist culture. Buoyed by the era's heightened interest in the expressive qualities of the body, these playwrights were highly invested in the authority of language, yet were drawn to the capacity of dance to evoke spiritual or psychological states which words could not completely capture. In its belief of fundamental correspondences among the arts, Symbolism encouraged experimentation across disciplines, and this study traces interconnections among many of its significant figures including Max Reinhardt, Claude Debussy, Gertrud Eysoldt, Edward Gordon Craig, Bronislava Nijinksa, Isadora Duncan, Jaques Dalcroze, Darius Milhaud, Vsevolod Meyerhold, Mariano Fortuny, Terence Gray, George Antheil, Eleonora Duse, and Michel Fokine."--Jacket